Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023) - Haris Al Farizi, Abdul; Kusmayadi, Iwan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to analyze the influence of investment decisions, funding decisions, and dividend policy on firm value: A case study of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period of 2019-2023. This research is an a associative study with quantitative. The sample was selected using the purposive sampling technique, resulting in 8 companies out of a total of 24 food and beverage companies listed on the IDX during the 2019-2023 period. Consequently, this study analyzes 40 observations. The panel data analysis method employed in this study is panel regression analysis using Eviews version 12. The results show that investment decisions, as measured by the Fixed Asset Ratio (FAR), have a positive and significant effect on firm value. Funding decisions, represented by the Debt-to-Equity Ratio (DER), also have a positive and significant effect on firm value. Meanwhile, the dividend policy, measured by the Dividend Payout Ratio (DPR), has a positive but not significant effect on firm value.